Irradiation damage on CrNbTaVWx high entropy alloys - Martins, Ricardo (2023)
ABSTRACT: CrNbTaVWx high-entropy alloys have been developed for plasma facing components to be applied in nuclear fusion reactors. The CrNbTaVWx (x = 1 and 1.7) compositions were prepared by ball milling and consolidated at 1600 degrees C under 90 MPa. To study the irradiation resistance of these materials, deuterium plasmas were used to irradiate the samples in the PF-1000U facility with 1 and 3 discharges. Structural changes before and after irradiation were analyzed by scanning electron microscopy coupled with energy dispersive X-ray spectroscopy. Nuclear reaction analysis was carried out with 1000 and 2300 keV 3He+ ion beams to evaluate the profile and amount of retained deuterium on the irradiated samples. After irradiation, the sample with higher W content revealed swelling and melting for all discharges, while in the case of CrNbTaVW only blisters were observed. The deuterium retention was higher for CrNbTaVW1.7 when compared with CrNbTaVW for 3 discharges applied.